2001
DOI: 10.1053/rapm.2001.23205
|View full text |Cite
|
Sign up to set email alerts
|

Regional block and mexiletine: The effect on pain after cancer breast surgery

Abstract: Regional block reduced the analgesic requirements in the early postoperative period, while mexiletine combined with regional block reduced the total analgesic requirements during the next 5 postoperative days. Although chronic pain was not affected by these treatments late-abnormal sensation may be diminished by combination of these treatments. Reg Anesth Pain Med 2001;26:223-228.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 10 publications
1
45
2
Order By: Relevance
“…For CPSP, local anesthetics may have clinical utility through early interruption of sensory information to the dorsal horn of the spinal cord [60]. The analgesic action from local anesthetics is based on the suppression of abnormal sodium channels that exist along injured neurons via cellular mechanisms such as the inhibition of G proteincoupled receptors and NMDA receptors [61,62].…”
Section: Local Anestheticsmentioning
confidence: 99%
See 2 more Smart Citations
“…For CPSP, local anesthetics may have clinical utility through early interruption of sensory information to the dorsal horn of the spinal cord [60]. The analgesic action from local anesthetics is based on the suppression of abnormal sodium channels that exist along injured neurons via cellular mechanisms such as the inhibition of G proteincoupled receptors and NMDA receptors [61,62].…”
Section: Local Anestheticsmentioning
confidence: 99%
“…Patients randomized to IV lidocaine were found to have significantly lower pain scores, with fewer patients developing CPSP (2/17 patients) or secondary hyperalgesia compared to patients randomized into the placebo group (9/ 19) at 3 months. Fassoulaki et al [60] evaluated the use of mexiletine in a pair of clinical trials. In a randomized, placebo-controlled trial, the incidence of CPSP and pain scores did not differ between study arms.…”
Section: Local Anestheticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation therapy may also induce injury, leading to microvascular insufficiency and fibrotic changes affecting the nerves and perineural tissues (13), with clinical painful manifestations ranging between 25 and 47% (14). Finally, surgery for diagnostic or therapeutic purposes, may lead to chronic pain as well, with incidence reaching high rates (60-90%) in some cases, such as after surgery for breast cancer (15)(16)(17)(18). Postmastectomy pain syndrome may be particularly troublesome and adversely impair the quality of life of female breast cancer survivors.…”
Section: The Pathophysiology Of Cancer Painmentioning
confidence: 99%
“…Studies by Fassoulaki et al have demonstrated that suitable perioperative analgesic regimens, mainly based on multimodal analgesic techniques, can significantly reduce the incidence and severity of chronic post-mastectomy pain in women after breast surgery for cancer (15)(16)(17)(18). These regimens are based on the concomitant perioperative use of gabapentin, sodium channel blockers (administered topically or systemically) and local anesthetics administered topically or in nerve infiltrations.…”
Section: Preventative Treatmentsmentioning
confidence: 99%